Intraocular Lens Power Calculation after Small Incision Lenticule Extraction - Luft, Nikolaus (Sci Rep, 2020)
With more than 1.5 million Small Incision Lenticule Extraction (SMILE) procedures having already been performed worldwide in an ageing population, intraocular lens (IOL) power calculation in post-SMILE eyes will inevitably become a common challenge for ophthalmologists. Since no refractive outcomes of cataract surgery following SMILE have been published, there is a lack of empirical data for optimizing IOL power calculation. Using the ray tracing as the standard of reference – a purely physical method that obviates the need for any empirical optimization - we analyzed the agreement of various IOL power calculation formulas derived from the American Society of Cataract and Refractive Surgeons (ASCRS) post-keratorefractive surgery online calculator. In our study of 88 post-SMILE eyes, the Masket formula showed the smallest mean prediction error [−0.36 ± 0.32 diopters (D)] and median absolute error (0.33D) and yielded the largest percentage of eyes within ±0.50D (70%) in reference to ray tracing. Non-inferior refractive prediction errors and ±0.50D accuracies were achieved by the Barrett True K, Barrett True K No History and the Potvin-Hill formula. Use of these formulas in conjunction with ray tracing is recommended until sufficient data for empirical optimization of IOL power calculation after SMILE is available.